Oscillation Criteria of Third-Order Nonlinear Impulsive Differential Equations with Delay - Xiuxiang Liu (Abstract and Applied Analysis)
This paper deals with the oscillation of third-order nonlinear impulsive equations with delay. The results in this paper improve and extend some results for the equations without impulses. Some examples are given to illustrate the main results.